Petrogenesis and geological significance of the Late Indosinian adakitic granites in the East Kunlun Orogen - WANG Bingzhang; LI Wufu; ZHENG Ying; WANG Chuntao; ZHAO Zhongguo; JIN Tingting; CAO Jinshan; FU Changlei (Dizhi lixue xuebao, 2024)
Objective  The Indosinian collision process of the East Kunlun Orogenic Belt remains a subject of debate. The newly discovered Triassic adakitic granites in the Xiaonanchuan area of East Kunlun provide new geological evidence that constrains the evolution of collisional orogenesis.   Methods  This study conducted petrological, geochemical, zircon U-Pb, and Lu-Hf isotopic analyses of the Moshigou and Bentoushan granitic intrusions in the Xiaonanchuan area to investigate their petrogenesis and tectonic settings. By integrating previous research on magmatism and sedimentation during the late Indosinian period within the East Kunlun Orogenic Belt, a preliminary discussion was conducted on collisional orogensis process.   Results and Conclusion  The Moshigou intrusion consists of granodiorite and monzogranite with zircon U-Pb ages of 209–208 Ma. The Bentoushan intrusion is composed of granodiorite with zircon U-Pb ages of 201–200 Ma. These granitoids have high SiO2 and Al2O3 contents and are rich in sodium. They also have high Sr contents (398×10−6–613×10−6) and Sr/Y ratios (50–97) and are depleted in heavy rare earth elements without Eu anomalies, exhibiting typical geochemical characteristics of adakitic rocks. The Moshigou granitoids have negative whole-rock εNd(t) (−3.60 to −3.34) and variable zircon εHf(t) (−1.3 to +5.9), indicating their derivation from the partial melting of the thickened lower crust. The Bentoushan granitoids have negative whole-rock εNd(t) (−1.65 to −1.55) and positive zircon εHf(t) (+3.4 to +7.3), suggesting their origin from meta-basic rock-dominated thickened lower crust with eclogite residue. Significance These results suggest that they were formed in a post-collisional extension setting. A comprehensive analysis indicates that the East Kunlun Orogenic Belt was in the collision and post-collision stages during the Late Triassic. The post-collision stage can be further divided into two phases of magmatic activity: early and late phases of the Late Triassic.